2004
DOI: 10.1530/eje.0.1510433
|View full text |Cite
|
Sign up to set email alerts
|

A thyroid nodule revealing a paraganglioma in a patient with a new germline mutation in the succinate dehydrogenase B gene

Abstract: A 32-year-old asymptomatic female was diagnosed with an isolated thyroid nodule of 2.5 cm diameter. Fine needle aspiration suggested a medullary thyroid carcinoma. Consequently, a total thyroidectomy was performed. The nodule stained positive for chromogranin A, neurone-specific enolase and synaptophysin, but not for calcitonin. Finally, pathological analysis showed a thyroid paraganglioma. Although the tumour appeared to be sporadic in a patient with no personal or familial history of paraganglioma and/or phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Although irradiation has been demonstrated to be effective for enlarging and symptomatic paragangliomas (12,13), an indication for primary radiotherapy is established rarely, and only if a surgical procedure is likely to involve a high risk of damage to several vessels and nerves (14). Moreover, as the present patient was negative for RET, SDHB or SDHD mutations (15,16), a left hemithyroidectomy without radiotherapy was appropriate.…”
Section: Discussionmentioning
confidence: 84%
“…Although irradiation has been demonstrated to be effective for enlarging and symptomatic paragangliomas (12,13), an indication for primary radiotherapy is established rarely, and only if a surgical procedure is likely to involve a high risk of damage to several vessels and nerves (14). Moreover, as the present patient was negative for RET, SDHB or SDHD mutations (15,16), a left hemithyroidectomy without radiotherapy was appropriate.…”
Section: Discussionmentioning
confidence: 84%
“…According to prior studies from three large multinational and/or multicenter cohorts (22,35,47), examining 110, 116, and 358 SDHB/SDHD mutation carriers respectively, only six thyroid tumors were identified: two PTCs (35), one thyroid PGL (47,48), as well as three thyroid tumors of unknown histopathology (22). Given the high PTC incidence rates (incidence of PTC estimated at 7.3/100 000) (49,50), it is no surprise that thyroid tumors are relatively frequently encountered as incidental findings in patients who are under active surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly due to the rarity and unexpected occurrence in the thyroid gland, this tumor type has remained underrecognized. A comprehensive search of the PubMed showed that only 35 cases have been reported in the English literature [1][2][3][4][5]. To better understand this rare entity, we undertook a brief review of the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Given these important implications, it is suggested that all patients with these rare tumors undergo possibly genetic testing. However, germline mutation testing in primary thyroid paraganglioma is seldom performed, with only one report by Zantour et al [1] discovering a new germline mutation in SDHB gene. We also failed to perform genetic testing of germline mutations in these genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation